q-Fibonacci statistical convergence - Atabey, Koray Ibrahim; Cinar, Muhammed; Et, Mikail (Walter de Gruyter Gmbh, 2025)
In this paper, we use the q-Fibonacci band matrix F q = ( F n k ( q ) ) to introduce the notions of q-Fibonacci summability, q-Fibonacci statistical convergence, strongly F q [ p ]-Ces & agrave;ro summability and give some inclusion relations about these concepts.
Keywords: band matrix; statistical convergence